2020
DOI: 10.1618/jhes.23.45
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on thermoregulatory and subjective responses during a 15-minute bath at 41 °C

Abstract: The purpose of this study was to clarify the effects of bathing on thermoregulatory and subjective responses in elderly persons compared to those in young persons. Ten young (20.4 years) and 10 elderly (69.7 years) individuals were asked to bathe for 15 minutes in water at 41 °C. Tympanic temperature (Tty) was measured using a thermometer with a thermistor, sweating rate (SR) was measured by a ventilated capsule method, and skin blood flow (SkBF) was measured by laser Doppler flowmetry to assess thermoregulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Fluctuations in the physiological response vary considerably depending on the hot water temperature, bathing time, room temperature, etc., the age difference in physiological fluctuations while performing JSB was summarized based on the following three experimental studies. The water temperature and immersion time reported by Nagasawa et al [44], Miwa et al [45], and Miwa et al [43] were 40 °C for 10 min, 40 °C for 20 min and 41 °C for 15 min, respectively. The water level of the bath was almost shoulder level in all three experiments.…”
Section: Effects Of Hot Water Immersion On Subjective and Physiologic...mentioning
confidence: 83%
See 2 more Smart Citations
“…Fluctuations in the physiological response vary considerably depending on the hot water temperature, bathing time, room temperature, etc., the age difference in physiological fluctuations while performing JSB was summarized based on the following three experimental studies. The water temperature and immersion time reported by Nagasawa et al [44], Miwa et al [45], and Miwa et al [43] were 40 °C for 10 min, 40 °C for 20 min and 41 °C for 15 min, respectively. The water level of the bath was almost shoulder level in all three experiments.…”
Section: Effects Of Hot Water Immersion On Subjective and Physiologic...mentioning
confidence: 83%
“…In addition, only young people complained of discomfort due to heat when the water temperature was 42 °C. Miwa et al [43] also compared the degree of warmth and discomfort of 10 elderly and 10 young people when they were soaked in hot water at 41 °C up to the chest for 15 min. For young people, while taking a bath, the changed from "slightly hot" or "hot", the elderly reported that it was almost "neutral. "…”
Section: Effects Of Hot Water Immersion On Subjective and Physiologic...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, limited assessment may be made in line with information shared in hot tub immersion studies monitoring BCT for different purposes. With immersion to nipple level, significant BCT increases compared to basal values were shown in the 15 th minute with tympanic temperature for people with coronary artery disease at 40 °C water temperature (~ 0.6 °C) (Allison et al 1993), in the 9 th minute for esophageal temperature in healthy people (~ 0.5 °C) (Allison and Reger 1992), and in the 15 th minute for tympanic temperature in 41 °C water temperature (in young people ~ 0.5 °C, in the elderly ~ 0.3 °C) (Miwa et al 2020). Another study observed a significant increase in tympanic temperature in the 10 th minute of head-out immersion in healthy people at 39 °C (~ 0.5 °C) (Koska et al 2003).…”
Section: Temperature Measurement Frequencymentioning
confidence: 91%
“…Additionally, a study with only 5 min BCT monitoring did not identify a significant variation in tympanic temperature at the end of 5 min with immersion to heart level in 40-41 °C water (Sugawara and Tomoto 2021). In light of this data, temperature measurement frequencies may be determined according to the targeted BCT increase value during balneotherapy practice considering that the proportion of BCT variation may change due to personal differences (Miwa et al 2020).…”
Section: Temperature Measurement Frequencymentioning
confidence: 99%